Implementasi Literasi Keuangan Dalam Meningkatkan Kinerja Usaha Kecil Kopi Aren Bandung Jawa Barat - Amelia Sugangga; Puji Handayati; Satia Nur Maharani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The owner of this Kopi Aren small business located in Bandung, in the application of financial literacy is more assisted by the Digitalization system or can be called financial technology, according to the explanation from the owner that this system is very helpful for performance, especially finance in the operation of daily operational activities. Digitalization is already a very important thing to use in its business. The purpose of this study is to determine the extent of the use of financial literacy in small businesses in Palm Coffee carried out by the owner. The research used is using the Qualitative method which is carried out by means of interviews and field observations in the application before and after financial literacy is applied. The results obtained from applying the concept of financial literacy turned out to be enough to improve their business, so that finances were more structured and clearer. Here it can be seen that the implementation for financial literacy is very useful for the progress of this small business business venture and can be applied to other small business businesses.